2018
DOI: 10.1155/2018/2709037
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Surface Energy and Adhesion Force of Polyethylene/Paperboard: A Predictive Tool for Quality Control in Laminated Packaging

Abstract: Poor adhesion continues to be a problem for manufacturers of laminated packaging. Therefore, the aim of this research was to study the effect of flame treatment, the type of coating, and starch application on the adhesion force of polyethylene/paperboard. The force of adhesion was determined using the peel test method; the paper surface energy was assessed by contact angle analysis; and paperboard roughness was determined by profilometer. The flame treatment did not affect the surface roughness but significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Our Raman analysis indicated that the amount of strain and thus possibly surface tension in the parylene C-coated graphene sample is higher than those of other samples. As reported in the literature 51 , there is a direct relation between the adhesion force (W) and surface tension (ɣ): W ~ ɣ. Consequently, more surface tension could possibly result in more adhesion force and thus better transfer of graphene…”
Section: Resultsmentioning
confidence: 94%
“…Our Raman analysis indicated that the amount of strain and thus possibly surface tension in the parylene C-coated graphene sample is higher than those of other samples. As reported in the literature 51 , there is a direct relation between the adhesion force (W) and surface tension (ɣ): W ~ ɣ. Consequently, more surface tension could possibly result in more adhesion force and thus better transfer of graphene…”
Section: Resultsmentioning
confidence: 94%
“…In contrast to other solution processes, using a low-surface free-energy elastomer cover during the thermal cross-linking process was intended to reduce the phase separation of the IGPEs with the impeding physical and chemical reaction between the elastomer material and the IGPE film, resulting in a structural organization of the ionic species and their efficient transport under the external electric field (Figure ). As the surface free energy is directly correlated with the adhesion property between the top stamp material and the bottom film, a low-surface-energy polymer material is a good candidate as the stamp material to minimize the adhesion between the stamp material and the IGPE film. Thus, a PDMS polymer was selected as the stamp layer material because PDMS not only has a relatively low surface free energy (23 mJ/m 2 ) and the lowest relative adhesion among various polymers but also provides smooth surface roughness via a facile solution process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is expected to positively influence the aspect ratio of the fabricated parts and reduce the number of rejected parts. The lowering of the surface energy of the steel-based molds will prevent the adhesion of polymers to the surface. In the present study, we studied the influence of the oxygen source (H 2 O and O 3 ) on the Al 2 O 3 and TiO 2 ALD processes by comparing the total surface energy of different coatings on steel substrates. Surface morphology and roughness were analyzed to verify if the coatings have a roughness below 30 nm, a requirement given by industry.…”
Section: Introductionmentioning
confidence: 99%